Perovskite Na0.5Bi0.5TiO3: a potential family of peculiar lead-free electrostrictors. Issue 22 (23rd May 2019) - Yin, Jie; Liu, Gang; Zhao, Chunlin; Huang, Yanli; Li, Zhitao; Zhang, Xingmin; Wang, Ke; Wu, Jiagang
Abstract : For perovskite ferroelectric oxides, the composition-induced transition from ferroelectrics to relaxors can enhance their electrostrictive coefficient Q 33 remarkably, and has been attracting more and more attention in recent years. Abstract : For perovskite ferroelectric oxides, the composition-induced transition from ferroelectrics to relaxors can enhance their electrostrictive coefficient Q 33 remarkably, and has been attracting more and more attention in recent years. Achieving a larger electro-strain response is one of the most original driving forces for pursuing higher Q 33 values, while the two are often incompatible. Herein, taking the promising relaxor ferroelectric Na0.5 Bi0.5 TiO3 (NBT) as the research object, we report the excellent electrostriction-like electro-strain behaviors (0.41% ≤ S uni ≤ 0.46%, 25 ≤ T ≤ 125 °C; S uni exhibits only 2.23% decline after 10 5 cycles) together with a series of enhanced Q 33 values (0.029–0.047 m 4 C −2 ). Accompanied by the reconstruction of de-coupled A–O interactions, the electric-field-induced relaxor to ferroelectric state transition contributes to the superior electro-strain behaviors, while the enhanced Q 33 will greatly degenerate during this transition process. In contrast to the non-hysteretic electrostriction observed in linear dielectrics, for NBT-based relaxor ferroelectrics, the peculiar coexistence of ferroelectric in-phase a 0 a 0 c + and anti-phase a − a − a − tiltings is suggested to contribute to the enhanced electrostriction-like behaviors observed in this work. These observations indicate that NBT-based systems can be considered as a potential family of peculiar lead-free electrostrictors for application in the field of actuators.